Automatic Valve-Rejection Algorithm for Cardiac Doppler Ultrasound Systems. (24th March 2013) - Baba, Tatsuro; Adachi, Shuichi; Taiko, Masatsugu
Abstract : In recent years, blood flow diagnosis using Doppler ultrasound systems has become popular. Using these systems, the peak velocity of blood flow is automatically traced. However, because valve signals are mixed with the blood flow signals in a heart chamber, automatic measurements of blood flow are not correctly recorded. To solve this problem, we developed a novel method that adopted system identification. We applied a mathematical model with an electrocardiographic waveform as the input and a trace waveform of the peak velocity as the output. Several mathematical models with different structures and orders were compared to select the optimal model. Using this model, we developed a system that could automatically eliminate the valve signal. We also evaluated our valve-rejection algorithm using simulations based on actual clinical data.